MEMBANGUN BUDAYA KERJA YANG PRODUKTIF: SEBUAH KAJIAN TEORISTIS - Deby Nuraini; Binta Zulfa Nafisa, Hilma Sri Wahyuni, Ajeng Mutiarananda Wahyuna, Aminah Yasin (Jurnal Ekonomi dan Bisnis, 2025)
The focus of this study is to theoretically examine how work culture, job satisfaction, and work discipline are related. The study uses a literature review method to collect data, which begins by identifying and synthesizing results from previous studies related to the subject. Furthermore, a theme approach was used to investigate the relationships between key variables. According to the results of the study, a productive work culture is strongly influenced by the level of happiness and discipline. One of the important findings of the research is that leaders have a very important role in creating a supportive work environment, and that employees should actively participate in the process of creating such a work environment. However, the shortcoming of this study is the lack of empirical data that supports its theoretical conclusions. As a result, the hypotheses suggested should be tested in various organizational contexts.